Children's Perspectives on their Economic Activity as a Pathway to Resilience - Coimbra Liborio, Renata Maria [UNESP]; Ungar, Michael (Wiley-Blackwell, 2010)
When viewed in the context of children's physical, social, and economic ecologies, children's work has both contextually specific benefits and consequences. This paper examines children's experiences of their economic activity using a theory of resilience as a contextually and culturally embedded phenomenon [British Journal of Social Work, 38 (2008) 218]. Though there is evidence that child labour is a potential threat to children's well-being, some forms of children's work may function as potential sources of health-enhancing resources associated with resilience, resulting in positive psychosocial development. Working children can find through their working experiences positive sources of efficacy and cohesion, strong identity, feelings of well-being, positive relationships, and access to material and social capital. (C) 2009 The Author(s). Journal compilation (C) 2009 National Children's Bureau and Blackwell Publishing Limited.
Keywords: adolescence; child development